PENGARUH MOTIVASI KERJA DAN DISIPLIN DIRI TERHADAP KEPUASAN DAN KINERJA KARYAWAN KANTOR KABUPATEN AINARO TIMOR LESTE - Rangel Sousa Simoes, Sebastiao Costa; Riana, Gde; Subudi, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
Employee performance is the result of work of employees in carrying out their duties in accordance with the responsibilities assigned. Motivation and self-discipline, is believed to be influenced on  satisfaction and performance excellence. This study aims to determine the effect of motivation and self-discipline to job satisfaction and employee performance. This study was conducted by taking of 50 respondents as a sample. Data were collected by using a questionnaire. Furthermore, the data that has been collected analyzed with path analysis. The analysis showed that the significant positive effect of motivation on job satisfaction and employee performance. Self -discipline is a significant positive effect on job satisfaction and employee performance. and job satisfaction significantly positive effect on employee performance.